INTEGRASI NILAI-NILAI EKOLOGIS DALAM TRADISI BANU NTT: STRATEGI PELAYANAN MISI KONTEKSTUAL" - Mada, Debby Yunita (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2024)
The East Nusa Tenggara (NTT) Islands are an area rich with unique traditions. One of them is the Banu Tradition which prohibits local people from taking natural products within a certain period of time. This is very relevant to environmental conditions in NTT where natural resource exploitation has begun to occur. The author uses qualitative methods through literature study using books, journals, articles and previous researchers to explore sources that are appropriate to this topic. The results of this research show that the Banu tradition can be a mission bridge and has ecological values that can benefit the environment and society. With this, the church can adopt the ecological values of the Banu tradition as a mission service that is contextual to NTT culture.